2021
DOI: 10.1016/j.envpol.2020.115859
|View full text |Cite
|
Sign up to set email alerts
|

Links between air pollution and COVID-19 in England

Abstract: In December 2019, a novel disease, coronavirus disease 19 (COVID-19), emerged in Wuhan, People’s Republic of China. COVID-19 is caused by a novel coronavirus (SARS-CoV-2) presumed to have jumped species from another mammal to humans. This virus has caused a rapidly spreading global pandemic. To date, over 300,000 cases of COVID-19 have been reported in England and over 40,000 patients have died. While progress has been achieved in managing this disease, the factors in addition to age that affect the severity a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
385
1
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 495 publications
(436 citation statements)
references
References 51 publications
37
385
1
13
Order By: Relevance
“…The importance of environmental public goods to the quality of life of a broad society had been stated in numerous recent scientific findings (Claeys et al, 2019; Elkerbout et al, 2020; Gatti, 2020; Gudi & Tiwari, 2020; Haines & Scheelbeek, 2020; Krenek, 2020; Travaglio et al, 2020). In scientific studies, major provided arguments stress the necessity to integrate environmental considerations into policies next to social and economic concerns (Claeys et al, 2019; Elkerbout et al, 2020; Haines & Scheelbeek, 2020; Kolovos, Kyriakopoulos, & Chalikias, 2011; Krenek, 2020; Radovanović, 2010; Zavalloni et al, 2019; Zhang, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of environmental public goods to the quality of life of a broad society had been stated in numerous recent scientific findings (Claeys et al, 2019; Elkerbout et al, 2020; Gatti, 2020; Gudi & Tiwari, 2020; Haines & Scheelbeek, 2020; Krenek, 2020; Travaglio et al, 2020). In scientific studies, major provided arguments stress the necessity to integrate environmental considerations into policies next to social and economic concerns (Claeys et al, 2019; Elkerbout et al, 2020; Haines & Scheelbeek, 2020; Kolovos, Kyriakopoulos, & Chalikias, 2011; Krenek, 2020; Radovanović, 2010; Zavalloni et al, 2019; Zhang, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…The spread of coronavirus in 2019–2020 around the world greatly accelerated the questions of environmental responsibility by giving evidence on how the world suffers from pollution and how quickly it recovers after key polluters are stopped (Gatti, 2020; Gudi & Tiwari, 2020). There have also been studies attempting to explain how harmony among people and nature can be ensured (Travaglio, Popovic, Yu, Leal, & Martins, 2020) and how important is rethinking the issues of climate change in the context of the Green Deal (Elkerbout et al, 2020). In this context, the role of each operating unit, especially, farmers who are directly affecting the environment in their economic activity, becomes especially important.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The clinical features of patients affected by COVID-19 have been extensively explored, but the predisposing factors contributing to increased transmission and clinical severity remains unclear. Social and ecological health determinants such as air pollution [2][3][4][5] , have been suggested to increase the risk of infection and exacerbate COVID-19 related illness. In addition, several comorbidities have been shown to increase COVID-19 mortality rates, including cardiovascular and respiratory pathologies 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent studies indicated that high concentrations of aerosol particles could significantly increase the susceptibility of COVID-19 infection and symptom aggravation in infected individuals (Accarino et al 2020 ; Fattorini et al 2020 ; Roviello et al 2020 ; Travaglio et al 2020 ). A known contributing factor is that airborne particles are capable of harboring pathogens by forming clusters with droplets and droplet nuclei and facilitate their long-distance transport (Alonso et al 2014 ; Zhao et al 2019 ).…”
Section: Transmission Of Covid-19 By Virus-laden Droplets and Indoormentioning
confidence: 99%